Can science fiction engagement predict identification with all humanity? Testing a moderated mediation model - Wu, Fuzhong; Zhou, Mingjie; Zhang, Zheng (Frontiers in Psychology, 2022)
Identification with all humanity (IWAH) is viewed as a critical construct that facilitates global solidarity. However, its origins have rarely been explored in previous literature, and no study has yet investigated the role of pop-culture in cultivating IWAH. To address this gap, this study initially focuses on science fiction (sci-fi), a specific pop-culture genre with worldwide audiences, and examines its effect on IWAH. It hypothesized a direct association between sci-fi engagement and IWAH from the narrative persuasion approach, and an indirect association via abstract construal based on the cognitive-literary approach. Moreover, the moderating role of actively open-minded thinking (AOT) in the direct and indirect association was also assessed. Results were obtained through a cross-sectional survey conducted in China (n=570) and showed that sci-fi engagement was positively associated with IWAH; this association was also partially mediated by abstract construal. Interestingly, and inconsistent with our hypotheses, AOT positively moderated the indirect effect but negatively moderated the direct effect. Theoretical and practical implications for cultivating IWAH from the media and pop-cultural perspective were discussed.